2017
DOI: 10.1038/ncomms14679
|View full text |Cite
|
Sign up to set email alerts
|

Hidden amorphous phase and reentrant supercooled liquid in Pd-Ni-P metallic glasses

Abstract: An anomaly in differential scanning calorimetry has been reported in a number of metallic glass materials in which a broad exothermal peak was observed between the glass and crystallization temperatures. The mystery surrounding this calorimetric anomaly is epitomized by four decades long studies of Pd-Ni-P metallic glasses, arguably the best glass-forming alloys. Here we show, using a suite of in situ experimental techniques, that Pd-Ni-P alloys have a hidden amorphous phase in the supercooled liquid region. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
46
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 49 publications
(63 reference statements)
4
46
0
2
Order By: Relevance
“…Moreover, there is currently no review that unites MGNs synthesized from different approaches (top-down and bottom-up) with conventional electrochemical reactions. To date, a wide range of BMG-forming alloys have been developed, including Zr-, [18] Fe-, [19] Cu-, [20] Ni-, [21] Ti-, [22] Mg-, [23] Pd-, [24] Au-, [25] and Pt-based compositions. Finally, as the first progress report on the metallic glass based electrocatalysts, we will also highlight some of the challenges that need to be addressed toward future progress in this field.…”
mentioning
confidence: 99%
“…Moreover, there is currently no review that unites MGNs synthesized from different approaches (top-down and bottom-up) with conventional electrochemical reactions. To date, a wide range of BMG-forming alloys have been developed, including Zr-, [18] Fe-, [19] Cu-, [20] Ni-, [21] Ti-, [22] Mg-, [23] Pd-, [24] Au-, [25] and Pt-based compositions. Finally, as the first progress report on the metallic glass based electrocatalysts, we will also highlight some of the challenges that need to be addressed toward future progress in this field.…”
mentioning
confidence: 99%
“…However, given the size of the supercell of about 8Å containing only 300 atoms, it is difficult for the system to form structural order on the nanometer length scale. Figure 6 depicts the simulated static structure factor, averaged over 10 configurations, along with the experimental structure-factor data from a recent differential scanning calorimetry (DSC) experiments, due to Lan et al 30 The static structure factor, S(q), can be obtained directly from the position of the atoms in the network:…”
Section: Resultsmentioning
confidence: 99%
“…(Color online) The static structure factors of Ni40Pd40P20 from AIMD simulations at 300 K and experiments. Experimental data are from differential scanning calorimetry measurements at 313 K due to Lan et al 30. …”
mentioning
confidence: 99%
“…SAXS provides an effective way to detect the phase separation in liquids. For example, recent in situ SAXS results have demonstrated that, unlike the former idea, there is almost no phase separation occurring above the glass transition ( T g ) and prior to the crystallization in a Pd–Ni–P metallic glass . At the beamline of sector 1, advanced photon source (APS), SAXS and XRD have been successfully incorporated together with the energy of 70 keV, which can be used to measure nanometer‐scale heterogeneity and atomic structural changes simultaneously in bulk metallic samples.…”
Section: Methods To Study the Structure Of Metallic Liquidsmentioning
confidence: 99%